2017
DOI: 10.7196/samj.2017.v107i2.10837
|View full text |Cite
|
Sign up to set email alerts
|

The influence of HIV infection on the age dependence of squamous cell carcinoma of the skin in South Africa

Abstract: Background. Cancer incidence typically increases with age, but it is not known whether ethnic characteristics influence the age dependence of squamous cell carcinoma of the skin (SCC). Objectives. (i) To determine the age dependence of SCC in the black African, coloured and white population groups of South Africa (SA); and (ii) to show whether any differences in the rate of change of age dependence could be influenced by diversity in behaviour and lifestyle, especially with regard to the prevalence of HIV infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…One attempt has been made to address this question as follows. As the average age at diagnosis of SCC in Black Africans in South Africa is about ten years younger than in the White and Coloured population groups, Diffey et al [44] demonstrated that the prevalence of HIV infection in the Black African population decreased the age at SCC diagnosis compared with the White and Coloured population groups.…”
Section: Risk Factors For the Development Of Skin Cancer In Southern mentioning
confidence: 99%
“…One attempt has been made to address this question as follows. As the average age at diagnosis of SCC in Black Africans in South Africa is about ten years younger than in the White and Coloured population groups, Diffey et al [44] demonstrated that the prevalence of HIV infection in the Black African population decreased the age at SCC diagnosis compared with the White and Coloured population groups.…”
Section: Risk Factors For the Development Of Skin Cancer In Southern mentioning
confidence: 99%
“…Fuzzy Inference System is incredibly helpful wherever probabilities for ambiguity could appear. It's employed in many aspects of daily life like automatically designed structure, computer Sci-Engineering, pharmaceutical structure, meteorology, and many more (Diffey,et. al., 2017).…”
Section: Introductionmentioning
confidence: 99%